Efficacy of triazole and strobilurin fungicides for controlling Fusarium Head Blight (Scab) and Brown rust of wheat in Punjab - BAGGA*, PARAMJIT S. (Indian Phytopathology, 2007)
Fusarium head blight (FHB or Scab) caused by Fusarium spp. has become an important constraint to wheat especially durum wheat production in Punjab since early 1990s.ln addition, the wheat cvs.PBW343 (which occupies more than 80% cultivated area in Punjab) and PBW 502 have also become susceptible to brown rust resulting in yield reduction. In the absence of resistant cultivars, the main approach for FHB and Brown rust control is the use of fungicides. Of the five bread wheat cvs. and three durum wheat cvs. Studied for their reaction to FHB ,the bread wheat cv. PBW 343 was consistently less affected, closely followed by PBW 502, showing a good level of field tolerance. The durum wheats were more affected and the durum cv. POW274 was rated as highly susceptible to FHB. Although, all the seven fungicides viz; Tilt, Score, Folicur, Topas, Amistar, Bayleton and Kavach ,evaluated as a single foliar spray at heading, significantly reduced FHB, Amistar (azoxystrobin) - a strobilurin fungicide, closely followed by the triazoles Folicur and Topas, was the most effective in reducing both FHB and brown rust diseases thus improving grain yield and quality.